Involvement of PI3K/Akt and p38 MAPK in the induction of COX-2 expression by bacterial lipopolysaccharide in murine adrenocortical cells - Mercau, María Elisa (2014)
Previous studies from our laboratory demonstrated the involvement of COX-2 in the stimulation of steroid production by LPS in murine adrenocortical Y1 cells, as well as in the adrenal cortex of male Wistar rats. In this paper we analyzed signaling pathways involved in the induction of this key regulatory enzyme in adrenocortical cells and demonstrated that LPS triggers an increase in COX-2 mRNA levels by mechanisms involving the stimulation of reactive oxygen species (ROS) generation and the activation of p38 MAPK and Akt, in addition to the previously demonstrated increase in NFκB activity. In this sense we showed that: (1) inhibition of p38 MAPK or PI3K/Akt (pharmacological or molecular) prevented the increase in COX-2 protein levels by LPS, (2) LPS induced p38 MAPK and Akt phosphorylation, (3) antioxidant treatment blocked the effect of LPS on p38 MAPK phosphorylation and in COX-2 protein levels, (4) PI3K inhibition with LY294002 prevented p38 MAPK phosphorylation and, (5) the activity of an NFκB reporter was decreased by p38 MAPK or PI3K inhibition. These results suggest that activation of both p38 MAPK and PI3K/Akt pathways promote the stimulation of NFκB activity and that PI3K/Akt activity might regulate both p38 MAPK and NFκB signaling pathways. In summary, in this study we showed that in adrenal cells, LPS induces COX-2 expression by activating p38 MAPK and PI3K/Akt signaling pathways and that both pathways converge in the modulation of NFκB transcriptional activity.